Prisoner in Al-Khobar : a true story about the life of an expatriate in the eastern province of Saudi Arabia during the 1990s /: a true story about the life of an expatriate in the eastern province of Saudi Arabia during the 1990s. (2018) - Norman, D. A
No abstract available